Overview of the Level of Knowledge and Behavior of Social Rehabilitation and Child Care Center (BRSPA) Officers in Bimomartani Regarding COVID-19 - Prastika Dica Izwara; Wulandari Berliani Putri (CV. Publikasi Indonesia, 2026)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus and was declared a global pandemic by the WHO in March 2020. The high number of cases in Indonesia, including in Sleman Regency, requires increased vigilance in various social institutions, including the Bimomartani Social Rehabilitation and Child Care Center (BRSPA), which has a child population that is highly vulnerable to infection. The transmission cases within the BRSPA environment demonstrate the importance of staff knowledge and behavior in preventing COVID-19. This study aims to describe the level of knowledge and behavior of Bimomartani BRSPA staff regarding COVID-19. This study used a quantitative descriptive design with a cross-sectional approach. The sample was drawn using a total sampling technique with 33 respondents. Data were collected through a validated questionnaire distributed online using Google Forms. Data analysis was conducted descriptively to illustrate the distribution of knowledge and behavior levels based on respondent characteristics. The study showed that 90.1% of respondents had good knowledge and behavior regarding COVID-19, while 9.9% had inadequate knowledge and behavior. Levels of knowledge and behavior were not evenly distributed across gender, age group, and education level. Furthermore, it was found that knowledge levels did not always align with preventive behaviors among some respondents. In general, Bimomartani BRSPA officers have good knowledge and behavior regarding COVID-19, but efforts are still needed to improve and equitably distribute health education to strengthen the consistent implementation of preventive behaviors.